Effects of Kamikihito and Unkei-to on Sleep Behavior of Wild Type and Parkinson Model in Drosophila - Ito, Kumpei; Kawasaki, Haruhisa; Suzuki, Takahiro; Takahara, Tsubasa; Ishida, Norio (Frontiers in Psychiatry, 2017)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and it is associated with sleep behavior disorders. In Drosophila melanogaster disease model, human α-synuclein A30P overexpressing fly (A30P PD model) have been shown for levy body aggregation and movement disorders. We measured sleep rhythms in the A30P PD model flies using the DAM system and found that they develop sleep defects at 20 days after eclosion. Furthermore, the total amount of sleep is significantly reduced in middle-aged PD model flies and the reduction has been attributed to nighttime sleep. The number and length of sleep bouts also decreased in middle-aged A30P PD model flies. Feeding of the oriental traditional herbal medicines (Kampo), Kamikihito and Unkei-to significantly ameliorate the level of sleep defects in A30P PD model flies. The Kamikihito and Unkei-to recovered 60-min sleep bouts number in the A30P PD model flies to the level of young (5 days after eclosion) flies. Kamikihito recovered sleep both in wild type and PD model flies. Unkei-to ameliorate not only sleep but also motor function in PD model flies. The data suggests that Kamikihito and Unkei-to might be uselul for the sleep defects in human PD patients as well as healthy human.